2012
DOI: 10.1182/blood-2011-12-397620
|View full text |Cite
|
Sign up to set email alerts
|

Loss of heterozygosity in 7q myeloid disorders: clinical associations and genomic pathogenesis

Abstract: Loss of heterozygosity affecting chromosome 7q is common in acute myeloid leukemia and myelodysplastic syndromes, pointing toward the essential role of this region in disease phenotype and clonal evolution. The higher resolution offered by recently developed genomic platforms may be used to establish more precise clinical correlations and identify specific target genes. We analyzed a series of patients with myeloid disorders using recent genomic technologies (1458 by single-nucleotide polymorphism arrays

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
109
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(117 citation statements)
references
References 32 publications
7
109
0
1
Order By: Relevance
“…A fundamental contribution to resolve this issue will surely be provided by new molecular technologies, for example, a SNP array study recently demonstrated that haploinsufficiency of defined 7q regions may translate to different clinical outcomes for MDS and AML patients carrying a 7q deletion and dysplastic features [36]. The IPSS [8], the Spanish MDS Cytogenetic Working Group [10] and another study [16] have reported that del(7q) and 27 present a similar poor OS and a similar high risk of MDS/AML evolution.…”
Section: Discussionmentioning
confidence: 99%
“…A fundamental contribution to resolve this issue will surely be provided by new molecular technologies, for example, a SNP array study recently demonstrated that haploinsufficiency of defined 7q regions may translate to different clinical outcomes for MDS and AML patients carrying a 7q deletion and dysplastic features [36]. The IPSS [8], the Spanish MDS Cytogenetic Working Group [10] and another study [16] have reported that del(7q) and 27 present a similar poor OS and a similar high risk of MDS/AML evolution.…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 27 patients, blasts were not increased and criteria for therapy-related myeloid neoplasms were not met in the diagnostic bone marrow sample at the time of del(7q) identification. This group included 10 patients (cases [13][14][15][19][20][21][22][23][24][25] with mild dysplasia, 16 patients (cases 16-18, 26-38) who did not have dysplasia and 1 patient in whom morphological assessment was difficult due to significant involvement by lymphoma (case 39) (Figure 1).…”
Section: Bone Marrow and Peripheral Blood Findingsmentioning
confidence: 99%
“…Two additional studies, using SNP array analysis on de novo and therapy-related myeloid neoplasms, identified CUX1 in the commonly deleted region of 7q22.1 (REFS 4,5). RNA sequencing and reverse transcription PCR analysis showed that CUX1 mRNA expression was reduced approximately twofold in leukaemic cells of affected patients 4,5 , and immunoblotting using a carboxy-terminal antibody showed that the fulllength CUX1 protein was reduced in AML cell lines with chromosome 7 and chromosome 7q loss karyotypes 5 . Reduced CUX1 mRNA expression was also documented in an AML sample that had a chimeric transcript containing CUX1 exon 1 upstream of claudin 7 (CLDN7) exons 2-4, probably resulting from a chromosomal translocation 5 .…”
Section: The Knudson Two-hit Modelmentioning
confidence: 99%
“…4). The complexity of 7q rearrangements suggests that multiple genetic factors, rather than a single tumour suppressor gene, contribute to the pathogenesis of myeloid disorders.…”
Section: The Knudson Two-hit Modelmentioning
confidence: 99%
See 1 more Smart Citation